2022
DOI: 10.1186/s12875-022-01730-x
|View full text |Cite
|
Sign up to set email alerts
|

Primary healthcare professionals’ perspectives on patient help-seeking for lung cancer warning signs and symptoms: a qualitative study

Abstract: Background Lung cancer is the leading cause of cancer incidence and mortality worldwide. Prompt patient help-seeking for signs and symptoms suggestive of lung cancer is crucial for early referral, diagnosis, and survivorship. However, individuals with potential lung cancer symptoms tend to delay help-seeking. This qualitative study explored perceived barriers to patient help-seeking and strategies to enhance help-seeking for lung cancer warning signs and symptoms from the perspective of primary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
1
8
0
Order By: Relevance
“…Participants who decided not to consult their GP cited concerns over wasting their own and the GP time and reported a high symptom tolerance threshold and a greater tendency to self-manage their symptoms 42 . These barriers are well documented in the wider literature 15 , 16 , 18 .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Participants who decided not to consult their GP cited concerns over wasting their own and the GP time and reported a high symptom tolerance threshold and a greater tendency to self-manage their symptoms 42 . These barriers are well documented in the wider literature 15 , 16 , 18 .…”
Section: Discussionmentioning
confidence: 90%
“…However, a Swedish study found that patients diagnosed with LC experience, on average, a 6-month delay between symptom onset and initiation of treatment 13 . Reasons for delayed patient help-seeking include patient factors, such as symptom misappraisal, fear of a potential cancer diagnosis, and guilt associated with smoking 14 , 15 , as well as healthcare system factors, such as the high financial cost of healthcare, lack of access to healthcare, and previous bad experiences with the healthcare system 15 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A qualitative study conducted by Weiss and colleagues [ 49 ] examined the implementation of decision analysis to facilitate the involvement of patients in decisions about their healthcare, and reported that only a few newly diagnosed hypertensive patients felt they were able to discuss issues with their doctor, and that most felt the physician did not have enough time. Barriers in consultations and decision-making have been reported by both physicians and patients [ 50 , 51 ], albeit more recent findings suggest that health professionals should be aware of the potential impact of patients’ feelings of guilt on consultations relating to the asymptomatic disease of hypertension [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…8 While emergent studies during the pandemic have reported high levels of patient satisfaction 9 with telehealth comparable to in-person appointments, males reported poorer experiences with telehealth than females. 10 Though some healthcare professionals have expressed concerns about misdiagnosing without in-person contact, 11 patients cite improved outcomes, increased accessibility, convenience, and decreased costs as reasons for their satisfaction with telehealth services. 12,13 Given these, telehealth may have the potential to engage men by reducing or addressing many of the aforementioned barriers men experience when accessing in-person health services.…”
Section: Introductionmentioning
confidence: 99%